Perancangan Aplikasi Koperasi Berbasis Android - Jones, Danzel Maxdriel Samuel; Sereati, Catherine Olivia; Christanto, Henoch Juli; Wijayanti, Linda; Mulyadi, Melisa (Jurnal Elektro, 2024)
The development of information technology cannot be separated from the use of mobile applications, which are increasingly varied. Mobile applications allow users to easily connect to internet services anywhere. Cooperatives are joint business entities that generally still use the manual method for recording members, transactions and so on, which can lead to human errors and time inefficiencies. The existence of a website-based cooperative mobile application that is implemented on smartphones using the Xamarin.Forms framework can reduce these problems. Smartphones will make online cooperatives more effective because they are portable, easy to use and more affordable.